Իգդիրի և Վանի շրջանի դամբարանների ճարտարապետությունը - Կիրակոսյան, Լյուբա (ԱրՊՀ հրատ․)
In this article there are represented the planning, structural and dimension features of stone tombs situated in Igdir and Van regions and which have been excavated during recent years (since 1997 year). Our surveys show that features of such tombs are characteristic to all kind of traditional structures of Van Kingdom situated in Armenian Highland.
Keywords: Դամբարաններ; Պատմություն; Ճարտարապետություն; Արցախ